Determinants of suicidal behavior among elders in Northwest Ethiopia: implications for prevention - Siraj, Seid; Belete, Habte; Beka, Michael; Shegaw, Maregu; Belete, Asmare; Birhan, Zelalem (Frontiers in Psychiatry, 2025)
BackgroundWorldwide suicide rates increases with age. Globally, suicidal behavior is a leading cause of injury and death. In many countries, older adult suicidal behavior is highly lethal because old people are unwilling to talk about their emotional problems and are less likely to report depression and suicidal thoughts. Exploring the phenomenon of suicide in the elderly in Ethiopia can provide a dependable source of reflection and add to the global aging, and suicide prevention conversation, generally in the low-income countries and middle-income countries (LMICs). This study aimed to assess the prevalence of suicidal behavior and its associated factors among elders in Bahir Dar city, Northwest Ethiopia.MethodA community-based cross-sectional study and multistage sampling technique were conducted among elders in Bahir Dar city. A systematic random sampling procedure was used to choose 626 elderly people over 65 years old in total who had lived in Bahir Dar city. Utilizing the revised Suicidal Behavior Questionnaire (SBQ-R), suicidal behavior was assessed. We quantify the related components using multivariable logistic regressions. The factors’ associations were delineated with odds ratios, 95% confidence intervals, and p-values that were deemed statistically significant at less than 0.05.ResultOverall, 12.8% (95% CI: 10.2, 15.3) of the population engaged in suicidal behaviors. The lifetime prevalence of suicidal ideation, plan, and attempts were 13.9%, 8.15%, and 1%, respectively. The prevalence of suicidal ideation in the past 12 months was 10.86%. The odds of being single (AOR: 2.19, 95% CI: 1.18, 4.06), having no social networks (AOR: 2.25, 95% CI: 1.01, 5.01), being depressed (AOR: 4.01, 95% CI: 1.97, 8.17), having a chronic illness (AOR: 3.03, 95% CI: 1.69, 5.44), and geriatric mistreatment (AOR: 7.81, 95% CI: 4.06, 15.05) were the independent predictors of suicidal behavior.ConclusionThe extent of suicidal behavior was found to be high in this study. The associated factors of suicide behavior include being unmarried, having a poor social network, having depression, chronic illness, and geriatric mistreatments. Therefore, clinicians should do routine mental health examinations for older persons, focusing on those who have a history of elder abuse or chronic illnesses, as these are major risk factors for suicide behavior. To detect and treat suicidal thoughts in elder populations, healthcare professionals should get culturally appropriate training. For legislators: create policies that address elder abuse by instituting community reporting mechanisms and legal protections for elder citizens, and give top priority to developing national healthcare initiatives that include elder-specific mental health and suicide prevention programs.